The Impact of Rurality and Age on Colorectal Cancer Screening Among Michigan Residents - Katherine Bromm; Antoinette B. Coe; Sarah E. Vordenberg (University of Minnesota Libraries Publishing, 2023)
Background: Colorectal cancer (CRC) is a prevalent cause of cancer-related deaths in Michigan, but not all Michigan adults had appropriate CRC screening. Objective: To assess the relationship between rurality and age on CRC screenings to inform how pharmacists could focus their efforts to educate, facilitate, or offer CRC health screenings. Methods: This was a retrospective, cross-sectional study using 2018 Michigan Behavioral Risk Factor Surveillance System (MiBRFSS) survey data. Michigan participants aged ≥ 50 years were included. Outcomes included the utilization of stool-based tests, sigmoidoscopies, colonoscopies, and the most recent CRC screening. Demographic variables included age, sex, income, race/ethnicity, relationship status, education level, employment status, income, rurality, and health insurance. Representative sampling weights were used to adjust for the complex survey design. Descriptive statistics, chi-square, and multivariable logistic regression analyses were conducted. IBM SPSS version 28.0.1.0 was used and an a priori p-value of <0.05 was deemed significant. Results: A weighted total of 3,762,540 participants were included, of which 21.3% (n = 781,907) reported living in a rural area and approximately 70% (n = 2,616,646) were between the ages of 50-69 years old. Most participants reported being White, non-Hispanic (n = 3,104,117, 84.5%), having health insurance (n = 3,619,801, 96.4%), and having a colonoscopy (74.6%, n= 2,620,581). There was no difference based on rurality. Compared to those aged 50-59 years, adults 60-69 years (AOR = 1.97, 95% CI: 1.58,2.45), 70-79 years (AOR = 3.29, 95% CI: 2.40,4.51), and ≥ 80 years (AOR = 2.23, 95% CI: 1.54,3.24) had higher odds of receiving a colonoscopy. Lack of insurance was associated with lower odds of receiving a colonoscopy (AOR = 0.38, 95% CI: 0.23, 0.56). Conclusion: Most participants reported having a CRC screening but efforts to increase CRC screening in Michigan adults aged 50-59 are warranted.